Study on three-dimensional shape measurement of partially diffuse and specular reflective surfaces with fringe projection technique and fringe reflection technique - Huang, Lei (2017)
Three-dimensional shape metrology using fringe projection technique and fringe reflection technique are effective ways to reconstruct three-dimensional shape for surfaces with different reflectance properties. Fringe projection technique is used for measuring objects with diffuse surfaces and relies on the principle of triangulation, while fringe reflectometry is used for specular reflective specimens based on principle of reflection. While fringe projection directly provides the profile, fringe reflectometry measures the slope of the surface from which the profile is integrated. In this study, the performance of these two fringe based techniques are investigated in relation to sensitivity and accuracy.